2012
DOI: 10.1016/j.ultrasmedbio.2012.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Transcranial Stimulation of Rat Abducens Nerve by Focused Ultrasound

Abstract: Non-pharmacological and non-surgical transcranial modulation of the nerve function may provide new opportunities in evaluation and treatment of cranial nerve diseases. This study investigates the possibility of using low-intensity transcranial focused ultrasound (FUS) to selectively stimulate the rat abducens nerve located above the base of the skull. FUS (frequencies of 350 kHz and 650 kHz) operating in a pulsed mode was applied to the abducens nerve of Sprague-Dawley rats under stereotactic guidance. The abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 38 publications
4
92
0
1
Order By: Relevance
“…To date, the focused LIPUS technique has been investigated to determine if it has the potential for non-invasive neuromodulation and modulation of region-specific brain activity. Specifically, Kim et al (2012) investigated the possibility of using focused LIPUS at 350 and 650 kHz to selectively stimulate the rat abducens nerve located above the base of the skull. In addition, Yoo et al (2011) reported that neuromodulation by focused LIPUS is involved in cellular excitability through regulation of ion channels and mechanoreceptors embedded within the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the focused LIPUS technique has been investigated to determine if it has the potential for non-invasive neuromodulation and modulation of region-specific brain activity. Specifically, Kim et al (2012) investigated the possibility of using focused LIPUS at 350 and 650 kHz to selectively stimulate the rat abducens nerve located above the base of the skull. In addition, Yoo et al (2011) reported that neuromodulation by focused LIPUS is involved in cellular excitability through regulation of ion channels and mechanoreceptors embedded within the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond thermal ablation, HIFU has notably been shown to allow safe, nondestructive, and transient focal blood-brain barrier disruption to facilitate drug delivery [24,25] and is being evaluated as a tool to induce hyperthermia to enhance the therapeutic effect of radiotherapy and chemotherapy [26][27][28]. Transcranial noninvasive HIFU has also been used to modulate cortex activity in a study with human volunteers [29] and to stimulate deep brain nuclei [30]. This makes HIFU potentially capable of combining lower ultrasound intensities for tissue stimulation monitoring before the application of higher intensities for ablation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that continuous-wave US can be more damaging to certain tissues as compared to pulsed-wave US, potentially due to rapid heating due to friction [Ziskin, 1993]. Currently, there is no clear indication of which technique may be more efficacious for NM, though it is likely that it is target specific, and further complicated by the depth of a tissue structure, the homogeneity of intervening tissue before the target, and the prevalence of mechanosensitive elements of the target cell type itself [Kim et al, 2012]. With regard to neural tissues specifically, both continuous-wave and pulsed-wave US have been found to be effective in modulating neural activity [King et al, 2013].…”
Section: Continuous Wave Versus Pulsed-wave Usmentioning
confidence: 99%